Liquidity Management Practices And Financial Stability In Sri Lankan Banks - Prathickshainy, F.; Muraleetharan, P. (Jaffna Science Association, 2025)
Liquidity management is a critical determinant of financial stability in the banking sector, particularly in the context of economic volatility and external shocks. This study examines the liquidity management practices and financial stability in Srilankan, using data from domestic Licensed Commercial Banks (LCBs),The study employs correlation and regression analyses to assess the relationship between liquidity management and financial performance metrics, including Return on Assets (ROA) and Return on Equity (ROE). The findings reveal a complex relationship between liquidity and profitability, with higher NPLs unexpectedly associated with increased returns, warranting further investigation. The regression models, however, show low explanatory power, indicating that traditional liquidity metrics may not sufficiently predict bank performance in the Sri Lankan context. The study underscores the need for banks to adopt dynamic liquidity management strategies that go beyond regulatory compliance to enhance resilience against economic instability. Policymakers and bank managers are urged to refine liquidity frameworks to safeguard financial stability, particularly in light of rising liquidity pressures and NPLs exacerbated by the COVID-19 pandemic and the 2022 economic crisis.
Keywords: Liquidity management; Financial stability; Non-performing loans (NPLs); Return on assets (ROA); Return on equity (ROE)